2015
DOI: 10.1177/0095798415578004
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Racial Socialization, and Positive African American Youth Development

Abstract: Positive youth development is critical for African American youth as they negotiate a social, political, and historical landscape grounded in systemic inequities and racism. One possible, yet understudied, approach to promote positive youth development is to increase African American youth consciousness and connection to their Africentric values and culture. The primary purpose of this article was to investigate the degree to which cultural and group consciousness factors (i.e., cultural orientation, Africentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 87 publications
3
54
0
Order By: Relevance
“…Consistent with prior research linking racial discrimination to poorer outcomes (e.g., Seaton & Douglass, 2014), we expected that daily racial discrimination will function as a risk factor and will be associated with less positive daily affect and more negative daily affect. Consistent with prior scholarship (Grills et al, 2016), we view positive racial socialization messages that instill self‐worth and racial pride in adolescents as serving as both compensatory (promotive) and protective resilience factors. As a result, we expected that when adolescents reported receiving self‐worth and racial pride messages, they will report more positive affect and less negative affect on the same day and following day.…”
Section: Racial Discrimination Experiences Among African American Adosupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with prior research linking racial discrimination to poorer outcomes (e.g., Seaton & Douglass, 2014), we expected that daily racial discrimination will function as a risk factor and will be associated with less positive daily affect and more negative daily affect. Consistent with prior scholarship (Grills et al, 2016), we view positive racial socialization messages that instill self‐worth and racial pride in adolescents as serving as both compensatory (promotive) and protective resilience factors. As a result, we expected that when adolescents reported receiving self‐worth and racial pride messages, they will report more positive affect and less negative affect on the same day and following day.…”
Section: Racial Discrimination Experiences Among African American Adosupporting
confidence: 83%
“…The emotional distress and reactivity adolescents experience when encountering stressful events such as racial discrimination has negative implications for adolescents’ psychological outcomes (Benner et al, 2018). Nevertheless, scholars highlight ways adolescents may be resilient, in spite of the reality of racial discrimination, through the racial and cultural resources they have in their environments, such as parental racial socialization (e.g., Grills et al, 2016). However, the ways that racial discrimination and racial socialization impact important adjustment outcomes in the short‐term, in youths’ day to day lives, are not well understood in extant research literatures due to overreliance on long‐term retrospective assessments.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the authors articulate the ''Black identity as promotive'' perspective, highlighting evidence of African Americans' historical values around education, including struggles to attain education for upward social mobility and positive community development. From this perspective, Black youth who strongly connect to their Black identity (high centrality) in ways that recognize their group's educational values and the racial biases faced by their group in educational pursuits (low public regard) may be motivated to succeed academically, especially in the face of their own race-related challenges (Grills et al, 2016;Lozada, Jagers, Smith, Banales, & Hope, 2017;White-Johnson, 2012).…”
Section: Racial Identity As a Promotive And Protective Factormentioning
confidence: 99%
“…Furthermore, Afrocentric values have been found to be positively related to academic self‐efficacy beliefs for elementary‐age students (Shin, ). Similarly, Grills, Cooke, Douglas, Subica, Villanueva, and Hudson () examined the relationship between cultural consciousness factors (i.e., Afrocentric values, cultural orientation, and racial socialization) and positive youth development outcomes. In this study, the results showed that Afrocentric values and cultural orientation predicted positive youth development outcomes.…”
Section: Identity Development and Black Youthmentioning
confidence: 99%